Analyzing Radiation Protection Risks in Nuclear Medicine: Cause Investigation and WSR-Based Countermeasure Evaluation - Sun P; Li G; Zhu Y (Risk Management and Healthcare Policy)
Peng Sun,1 Guanting Li,2 Yunhe Zhu1 1Department of Nuclear Medicine, Renmin Hospital, Hubei University of Medicine, Shiyan, Hubei, People’s Republic of China; 2Research School of Physics, The Australian National University, Canberra, ACT, AustraliaCorrespondence: Yunhe Zhu, Email zjkc139@163.comObjective: To analyze and investigate the causes of radiation protection safety risks in nuclear medicine diagnosis and treatment, formulate radiation protection safety management countermeasures, and evaluate their effectiveness.Methods: In October 2020, the Department of Nuclear Medicine at our hospital established a radiation protection safety management team, utilizing association rules to investigate and analyze the causes of radiation protection safety risks. A Wuli-Shili-Renli (WSR) system management approach was implemented, addressing physical (Wuli), procedural (Shili), and human factors (Renli) to improve technical safeguards, optimize processes, and enhance personnel awareness. A total of 1200 patients receiving diagnosis and treatment were divided into two groups. The control group (600 cases) used standard inspection-based radiation protection, while the observation group (600 cases) adopted WSR system management in addition to standard measures. Radiation protection risk control effectiveness and safety control capability scores were compared between the two groups.Results: The proportions of excessive diagnostic doses and additional radiation harm in the observation group were both lower than those in the control group (P < 0.05); the proportions of risk sources, including building environment, protective measures, dose monitoring, safety awareness, and waste disposal, in the observation group were all lower than those in the control group (P < 0.05). The observation group’s scores in radiation protection theory, practical risk management skills, and radiation protection safety literacy, as well as the total score, were higher than those of the control group (P < 0.05).Conclusion: The WSR system management approach effectively reduces radiation protection safety risks, improves the diagnostic and therapeutic environment, minimizes radiation exposure to patients and staff, and enhances safety risk management levels in nuclear medicine departments.Keywords: nuclear medicine, radiation protection, radiation safety, risk management, safety management, association rule learning, Wuli-Shili-Renli framework